The impact of AI anchor anthropomorphism on users’ willingness to co-create value in tourism live-streaming contexts: the mediating role of social presence and the moderating role of perceived control - Ye, Qiongwei; Li, Yuting; Luo, Yumei; Pang, Zhilin (Frontiers in Psychology, 2026)
With the advancement of large language models and multimodal interaction technologies, AI anchors capable of substituting human hosts have been increasingly applied in the live streaming e-commerce field, demonstrating anthropomorphic characteristics that extend beyond physical appearance. Among these applications, the impact of the anthropomorphism level of AI anchors on users’ willingness to engage in human–machine value co-creation in tourism live streaming contexts remains an underexplored yet critical area. Existing studies mostly focus on the impact of anthropomorphism on purchase intention, but overlook the underlying mechanism in high-interaction contexts. Grounded in the social response theory, social presence theory and self-determination theory, this study investigates tourism live streaming as a contextual setting through experimental designs involving two levels of anthropomorphism (high vs. low). It systematically examines the impact of AI anchor anthropomorphism on users’ willingness to co-create value, the mediating role of social presence, and the moderating role of perceived control. The findings indicate that: (1) The level of anthropomorphism exhibited by AI anchors significantly and positively influences users’ willingness to participate in human–machine value co-creation, with participants in the high anthropomorphism condition reporting significantly greater willingness than those in the low anthropomorphism condition; (2) Social presence mediates this relationship; and (3) Perceived control negatively moderates the path between anthropomorphism and social presence—higher perceived control attenuates the positive effect of anthropomorphism on social presence, but does not moderate the direct relationship between anthropomorphism and willingness to co-create. This study elucidates users’ dual psychological needs for “social connection” and “autonomous control” in human–machine collaborative settings, highlights the importance of balancing these competing demands, and offers both theoretical insights and practical implications for the design of AI-driven interactions in tourism live streaming.